(−)-4-O-(4-O-β-D-glucopyranosylcaffeoyl) quinic acid enhanced the efficacy of anti-PD-L1 against esophageal carcinoma through inhibiting PI3K pathway. (2nd November 2021) - Song, GuangLin; Lu, YanLing; Tang, LiNa; Li, Min; Yin, Jie; Chen, HongMing; Ling, JunDa
Abstract: Purpose: Using antibodies to block the programmed cell death 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) pathway as an immunotherapy has achieved great success in the clinical treatment of various types of carcinoma. However, the efficacy is limited because of tumor-mediated immune immunosuppression and evasion. This study demonstrated that inhibiting the PI3K pathway with (−)-4- O -(4- O - β - D -glucopyranosylcaffeoyl) quinic acid (QA), a new compound from endophytic fungus Penicillium citrinum of Avicennia marina, enhanced the therapeutic efficacy of anti-PD-L1 antibody against esophageal tumors. Materials and methods: mEC25 cells were injected into C57BL/6 mice to establish a syngeneic esophageal tumor model. Tumor infiltration lymphocytes (TILs) were analyzed by flow cytometry. Gene and protein expression was detected by qPCR and western blot, respectively. Moreover, the therapeutic effects of QA combining with anti-PD-L1 antibody were evaluated in the tumor model. Results: These data demonstrated that inhibition of PI3K with QA could overcome immunosuppression and promote the response of T-lymphocytes, resulting in the restoration of cytotoxic T cell-mediated tumor control. QA and anti-PD-L1 combination therapy significantly delayed tumor growth. Conclusions: Our results provide a scientific basis to develop combination therapies involving anti-PD-L1 and PI3K inhibitors to improve responses in patients with esophageal cancer.